Clinical and diagnostic evaluation of finished cattle exposed to beta adrenergic agonists and physical exertion - Frese, Daniel A. (Kansas State University, 2015)
The widespread use of beta adrenergic agonists in beef cattle production has been adopted by the beef industry in recent years to improve weight gain and feed efficiency at the end of the feeding period. During this feeding period, anecdotal reports of increased mortality during the timeframe in which beta agonists were being fed to cattle was also reported, and confirmed in epidemiologic studies. Additionally, adverse animal welfare events at abattoirs in cattle fed beta adrenergic agonists were reported in August 2013. The objectives of this dissertation were to investigate physiologic and management factors that may be associated with adverse effects of the use of beta adrenergic agonists in cattle. Two studies were conducted, one to establish normal Holter monitor registration values and evaluate the electrocardiographic effects of zilpaterol and ractopamine hydrochloride on finishing steers, and one to develop a model to investigate the physiologic effects of forced exercises in finished cattle, which was hypothesized to be a possible factor in reported adverse cattle welfare events in August 2013. Thirty steers were enrolled to evaluate the effect of ractopamine, zilpaterol or negative control on arrythmia and mean heart rate at 4 different time periods during a 28 day feeding period. Cattle fed ractopamine and zilpaterol had increased heart rate (P < 0.05) but no differences in arrythmia rates were found. Forty steers were enrolled in a study at a commercial feeding facility to develop a model for fatigue in cattle forced to run 1,540 m compared to control cattle walked 1,540 m. Blood lactate, cortisol, rectal temperature, heart rate was increased (P < 0.05), blood pH decreased (P < 0.01) and to have reduced locomotion, as measured by pedometers, during the 48 hour period following handling compared to controls. Additionally cattle that were fatter and forced to run had increased lactate (P =0.057) and lower blood pH (P < 0.01) than thinner cohorts. Cattle handling method is a factor in the health and welfare of cattle and the continued adoption of low stress handling methods throughout the beef industry should be pursued.
Keywords: Cattle; Beta Agonists; Fatigue; Exercise; Electrocardiogram; Veterinary Medicine (0778)